Does the sustainable fiscal policy foster its credibility? - Haryo Kuncoro (Economic Journal of Emerging Markets, 2017)
This paper examines the credibility and sustainability of fiscal policy in the case of Indonesia. The standard model of fiscal sustainability is modified to accommodate the credibility aspect. The empirical estimates are done by employing several aspects of the time series econometric literature including unit roots, degree of integration, co-integration, and stability tests. Based on the deficit forecast error reaction function, we estimate the quarterly data over the period 2001-2013 relying on the autoregressive distributed lag model. The results present that the deficit rule policy is not credible while central government's debt is unsustainable. The coexistence of non-credibility and unsustainability of fiscal policy in Indonesia is also closely related to the world oil prices and trade openness fluctuations. Under these strong external circumstances instability, the fiscal authority credibility plays an important role in conducting fiscal rule policy which operates primarily through a signalling effect.